Effects of high-intensity exercise repetition number during warm-up on physiological responses, perceptions, readiness, and performance - Fujii, N.; Fujisawa, K.; Dobashi, K.; Cao, Y.; Matsutake, R.; Lai, Y. F.; Nishiyasu, T. (Research Quarterly for Exercise and Sport, 2023)
Purpose: We investigated whether varying the number of repetitions of high-intensity exercise during work-matched warm-ups modulates physiological responses (heart rate, metabolic responses, and core temperature), perceptions (ratings of perceived exertion, effort of breathing), readiness for exercise, and short-term exercise performance. Methods: Ten physically active young males performed a 30-s Wingate anaerobic test (WAnT) following a warm-up consisting of submaximal constant-workload cycling at 60% maximal oxygen uptake with no high-intensity cycling (constant-workload warm-up) or with 1, 4, or 7 repetitions of 10 s of high-intensity cycling at 110% maximal oxygen uptake. All warm-ups were matched for duration (10 min) and total work. Results: Warm-ups with seven repetitions of high-intensity cycling resulted in higher ratings of perceived whole-body exertion and effort of breathing than the constant-workload warm-up. Warm-up with four repetitions of high-intensity cycling produced greater readiness for a 30-s WAnT (7.33 ± 0.73 AU) than the constant-workload warm-up (6.33 ± 0.98 AU) (P = .022). Physiological responses did not differ among the four warm-up conditions, though peak heart rate was slightly higher (~5 beats/min) during warm-up with four or seven repetitions of high-intensity cycling than during the constant-workload warm-up. Peak, mean, and minimum power output during the 30-s WAnT did not differ among the four warm-up conditions. Conclusions: These results suggest that the effects of warm-ups with intermittent high-intensity exercise on physiological responses and short-term high-intensity exercise performance do not greatly differ from a warm-up with a work-matched submaximal constant-workload. However, they appear to modulate perceptions and readiness as a function of the number of repetitions of the high-intensity exercise.